Моделювання дійснозначних кореляційних функцій з урахуванням комплексного спектру - Черемська, Надія Валентинівна (НТУ "ХПІ", 2017)
Отримано зображення для дійснозначних кореляційних функцій нестаціонарних випадкових послідовностей, процесів та полів з використанням трикутних моделей операторів для різних випадків спектру. Отримані зображення дійснозначних кореляційних функцій випадкових послідовностей та процесів можуть використовуватися для аналізу статистично нестаціонарних даних.

There is a large class of applications for which statistical transience is characteristic. The examples are: proliferation of waves in a turbulent atmosphere, the study of electromagnetic waves propagating near the globe or in the ionosphere, the analysis of the problem of growth or attenuation of surface waves by strong turbulence generated by a moving object, and others. In solving such problems the use of models of stationary random processes or homogeneous random fields leads to some errors. Thus one needs to develop the correlation theory for a broad class of non-stationary vector-valued random functions that would be promising for solving applied problems for which statistical heterogeneity or transience of relevant statistical data is essential. In this article, we obtain representations for the real-valued correlation functions of nonstationary random sequences, processes, and fields using triangular models of operators for various cases of the spectrum. The obtained representations of the real-valued correlation functions of random sequences and processes can be used to analyze statistically unsteady data.
Modeling of real-valued correlation functions with allowance for the complex spectrum
Keywords: статистична нестаціонарність; прикладні задачі; трикутні моделі операторів; випадкові коефіцієнти; статистично нестаціонарні дані; correlation function; triangular models of operators; nonstationary random sequences and processes